ERKIN TUSHISH TEZLANISHINI VIDEOCOM YORDAMIDA OʻRGANISH - Jalekeshov, A.S.; Turekeev, X.S. (SCIENCE and SOCIETY, 2025)
There are several ways to determine the acceleration of free fall. The results obtained are theoretically comparable with the calculated values.